Pengaruh Style Kepemimpinan, Komunikasi dan Motivasi Kerja terhadap Kinerja Karyawan Departemen Sample Room Di PT. XYZ - Ina Triweni; Yunita Primasanti; Anita Oktaviana Trisna Devi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the influence of leadership style, communication and work motivation on employee performance at PT XYZ. This research used a quantitative approach by distributing questionnaires to respondents. The population was 507 respondents. The sample used 223 respondents. The sampling method is probability sampling with a purposive sampling technique. The analysis used the validity test and reliability test of the Partial Least Square (PLS) program version 4.0 based on the Structural Equation Modeling (SEM) approach. The results show that leadership style does not affect employee performance while communication and work motivation have a positive effect on employee performance.